2010 Mexico Enterprise Survey : Country Highlights - World Bank (Washington, DC, 2014)
The World Bank interviewed a representative sample of the private sector in 8 of the most active economic regions in Mexico. The sample consisted of 1480 business establishments surveyed from August 2010 through June 2011. The enterprise survey covers several topics of the business environment as well as performance measures for each firm. This report presents following highlights from the survey: Mexican firms added jobs at over 5 percent but saw only modest gains in sales and productivity; however, productivity growth was due to gains from Mexico's small firms; Mexican firms cite informality, tax rates, access to finance, and crime as top obstacles; a greater proportion of Mexican firms face competition from the informal sector; Mexican firms exhibit lower levels of access to financial intermediation; and while losses due to crime in Mexico are high significantly fewer firms actually pay for security.